Impact germination in the content of the chemical components of Homs and sensory qualities of Biskt plant it, (Baghdad Science Journal, 2005)
This study was conducted to identify the impact of germination in the ratio Almaah of Chemical Constituents of Homs and in the organoleptic properties of the Biskt plant it and compare the results with the treatment control (seeds Almnepth) Adhrt results for a significant increase in the percentage of crude protein with the progress of the process of germination, reaching 24.5% in percentage of crude protein with the progress of the germination process Krbu hydrate college during the germination period, reaching 59.2% in the fourth day